The Challenges of Algorithm-Based HR Decision-Making for Personal Integrity - Leicht-Deobald, Ulrich; Busch, Thorsten; Schank, Christoph; Weibel, Antoinette; Schafheitle, Simon; Wildhaber, Isabelle; Kasper, Gabriel (Journal of business ethics, 2019)
Organizations increasingly rely on algorithm-based HR decision-making to monitor their employees. This trend is reinforced by the technology industry claiming that its decision-making tools are efficient and objective, downplaying their potential biases. In our manuscript, we identify an important challenge arising from the efficiency-driven logic of algorithm-based HR decision-making, namely that it may shift the delicate balance between employees' personal integrity and compliance more in the direction of compliance. We suggest that critical data literacy, ethical awareness, the use of participatory design methods, and private regulatory regimes within civil society can help overcome these challenges. Our paper contributes to literature on workplace monitoring, critical data studies, personal integrity, and literature at the intersection between HR management and corporate responsibility.